Analysis of LncRNA-mRNA Co-Expression Profiles in Patients With Polycystic Ovary Syndrome: A Pilot Study - Sun, Xiuhong; Liu, Yishan; Gao, Xinyu; Du, Mengxuan; Gao, Mengge; Zhong, Xingming; Wei, Xiangcai (Frontiers in Immunology, 2021)
Purpose This study aimed to investigate the profiles of messenger RNAs (mRNAs) and long noncoding RNAs (lncRNAs) in peripheral blood samples collected from polycystic ovary syndrome (PCOS) patients. In addition, an in-depth bioinformatics analysis regarding the lncRNA-mRNA co-expression network was performed. Methods High-throughput sequencing was used to measure the profiles of mRNAs and lncRNAs expressed in the peripheral blood samples isolated from six patients (three patients with PCOS and three normal women). In addition, five differentially expressed lncRNAs were chosen to validate the results of high-throughput sequencing by quantitative RT-PCR (qRT-PCR). Furthermore, a lncRNA-mRNA co-expression network was constructed using the Cytoscape software. Results A total of 14,276 differentially expressed mRNAs and 4,048 differentially expressed lncRNAs were obtained from the microarray analysis of PCOS patients and healthy controls (P < 0.05, Fold change >2.0).The qRT-PCR results were consistent with the data obtained through high-throughput sequencing. Gene ontology (GO) and KEGG pathway analyses showed that the differentially expressed mRNAs were enriched in the chemokine signaling pathway. In addition, the analysis of the lncRNA-mRNA co-expression network of the chemokine signaling pathway showed the involvement of 6 mRNAs and 42 lncRNAs. Conclusion Clusters of mRNAs and lncRNAs were aberrantly expressed in the peripheral blood of PCOS patients compared with the controls. In addition, several pairs of lncRNA-mRNAs in the chemokine signaling pathway may be related to PCOS genetically.